Cognição incorporada : sobre a construção de uma relação entre a ciência cognitiva e a experiência humana - Rosauro, Pedro Gabriel (2020)
This dissertation deals with the need to establish a relationship between cognitive science research and human experience research. To accomplish this task, the themes of phenomenology will be approached, particularly, the concepts of phenomenology by Merleau-Ponty, with regard to perception and the body itself. To complement the description of human experience, Buddhist philosophy will be addressed, with a focus on meditative practice. After this process, the different areas of cognitive science, such as cognitivism, connectionism and the enactive theory, will be themed, with the objective of arriving at the concept of embodied mind, which aims to build a parallel between cognitive science and human experience. To broaden the notion of embodied mind, Santiago's theory of cognition will be discussed. A philosophy of the non-self will also be addressed, as another point of convergence between science and experience. Following the path of the dissertation, consciousness will be investigated from a systemic point of view. And, finally, two schools of study of consciousness will be examined, neurophenomenology and the phenomenology naturalization project.